Compression of the lower trunk of the brachial plexus by a cervical rib in two adolescent girls: case reports and surgical treatment - Dahlin, Lars B; Backman, Clas; Düppe, Henrik; Saito, Harukazu; Chemnitz, Anette; Abul-Kasim, Kasim; Maly, Pavel (Journal of Brachial Plexus and Peripheral Nerve Injury, 2009)
Presence of a cervical rib in children is extremely rare, particularly when symptoms of compression of the lower trunk of the brachial plexus occur. We present two cases with such a condition, where two young girls, 11 and 16 years of age were treated by resection of the cervical rib after a supraclavicular exploration of the lower trunk of the brachial plexus. The procedure led to successful results, objectively verified with tests in a work simulator, at one year follow-up.